Spinal intradural arachnoid cysts Spinale intradurale Arachnoidalzysten - Stern, Y.; Spiegelmann, R.; Sadeh, M. (Neurochirurgia, 1991)
Three patients with indural spinal arachnoid cysts presented with back or neck pain of several months' duration. They gradually developed weakness and difficulty in Walking followed by rapid deterioration with signs of spinal cord or nerve root compression. Radiological studies showed a posteriorly located mass in the cervical, dorsal and lumbar region; one cyst filled with contrast medium and the diagnosis of the others was made at Operation. Surgery resulted in full recovery of two patients and partial recovery of the third.3 Patienten mit intraduralen spinalen Arachnoidalzysten hatten Rücken- bzw. Nackenschmerzen für mehrere Monate. Sie entwickelten allmählich Schwäche in den Beinen und Schwierigkeiten beim Gehen, gefolgt von einer rapiden Verschlechterung mit Zeichen der Wurzel- oder myelären Kompression. Radiologische Untersuchungen zeigten eine dorsale lokalisierte Raumforderung in der zervikalen, thorakalen oder lumbalen Region. Eine Zyste füllte sich mit Kontrastmittel, die Diagnose der anderen erfolgte während der Operation. Die chirurgischen Ergebnisse zeigten eine völlige Wiederherstellung bei zwei Patienten und eine teilweise Erholung bei einem Patienten.
Keywords: Spinal arachnoid cysts; Spinal cord compression